PENEGUHAN SECARA KONVENSIONAL DAN MOLEKULER ISOLAT Pseudomonas anguilliseptica SERTA PATOGENITAS PADA IKAN MAS (Cyprinus carpio) - , Ajeng Aekanurmaningdyah; , Prof. drh. Kurniasih, MV.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pseudomonas anguilliseptica caused Red Spot Disease (Sekitten - Byo) resulted very high mortality in fishes and serious economic losses as a Quarantine Fish and Diseases group I. Aims this study to identify Ps. anguilliseptica with conventional and molecular and the pathogenicity changes based on histopathology. This study used an isolate of Ps. anguilliseptica were identified by conventional and molecular methods. Conventional identification of morphologically and biochemically. Molecular identification by amplification 16S rRNA fragment using forward primer Psan-F (21-mer: 5'- TTGGGAGGAAGGGCA-GTAACC-3 ') and reverse Psan-R (20-mer: 5'- TGCGCCACTAAAATCTCAAG-3'), and sequencing. Pathogenicity test used 18 fishes divided by 2 groups each group consist of 9 fishes. Group I, fishes infected intramuscularly with buffer saline as a control and group II, fishes infected intramuscularly 0.1 ml LC-50 suspension of Ps. anguilliseptica as atreatments. Fishes has been euthanasia on 1st day, 8th day and 15th day after infection. The results of conventional identification showed that the morphology of the colonies appear round, grayish, convex, entire, diameter about 1 mm with rod-shaped cells and Gram negative. Biochemical results showed a positive reaction to oxidase, catalase, motility, gelatinase, pH 5.3 to 9.7, and sucrose